Who wants to work in bureaucracy? Career intentions of post-millennial students. Issue 1 (March 2019) - Jäkel, Tim; Borshchevskiy, George Alexander
This article investigates who wants, or does not want to work in Russian public administration, and why. A majority of Russians believe that public servants are concerned with improving their personal well-being rather than serving the public interest. Understanding working sector choices is thus the first step to attract talent into the civil service. We study public employment intention among a group of students of public administration in two elite Moscow universities who are relatively early undergraduates. Parents working in the civil service are the most important public sector career motivators of students in Russia, more important than positive perceptions of public sector compensation and its impact on society. Our findings imply that early-stage career plans are shaped outside university lecture rooms. We conclude that teaching public administration in Russia will have to focus on drawing a line between behavior that falls below standards of the profession and efforts to contribute to the well-being of citizens.